Managing Children during a Radiological or Nuclear Emergency—Canadian Perspectives. (May 2015) - Li, Chunsheng; Hauck, Barry; Fraser, Alan; Burton, Gordon; Cousins, Tom; Mahilrajan, Tim; Tracy, Bliss; Richards, Audrey; Sallafranque, Rosanne; Conway, Brenda; Lemyre, Louise; Kramer, Gary H.
Abstract : Abstract: Children have a higher chance of being contaminated by radioactive materials during a radiological or nuclear (RN) emergency. They are more sensitive to radiation health effects and suffer more significant psychosocial impacts than adults during emergency response. This paper presents a summary of recommendations on effective management of children during an RN emergency. These recommendations intend to be additional considerations for existing RN response protocols and procedures implemented at local, state/provincial, or national level.